How does customer co-creation affect firm’s brand image and customer’s willingness to pay a price premium? - LI, Yingnan (2015)
This study is aimed to investigate whether brand image and customer willingness to pay a premium can be affected by co-creation. Co-creation now has been a crucial part in firm‟s new product or service development process and a major factor of firm‟s competitive advantage. However, regarding the correlations between co-creation, brand image and willingness to pay a premium, most previous studies focused on co-creation effects on service-intensive industries, whereas the effects on new product development receive less attention. This study focuses on analysing the effects of co-creation on new product development rather than services. 282 respondents are involved in this study. They are tested purely by questionnaires. Co-creation is tested based on two measurements: „the degree of co-creation‟ and „satisfaction with co-creation experience‟. The results of this study show that: (1) The degree of co-creation is positively related to brand image. (2) Consumer satisfaction with co-creation experience is positively related to brand image. (3) The degree of co-creation is positively related to consumer WTP a price premium. (4) Consumer satisfaction with co-creation experience is positively related to their WTP a price premium. Further analysis based on each questionnaire items concludes several implications for managers. (1) Companies should identity deficient products and identify potential talented co-creators. (2) Companies should pay more attention for co-creation support. (3) Companies should maintain a stable relationship with consumers. (4) Companies should recognize different kinds of motivation system in order to establish the most suitable strategy for customer co-creation. (5) Companies should invest more in signalling activities, customize co-creation services and communications.